Discricionariedade administrativa neoconstitucional - Rodrigues, Willian Gustavo (2025)
This dissertation critically analyzes administrative discretion within the context of neoconstitutionalism, exploring the challenges and advancements introduced by this paradigm in the Brazilian legal system. It is based on the hypothesis that neoconstitutionalism, by expanding judicial control, has significantly advanced the protection against administrative abuses and the realization of fundamental rights. However, it also raised questions about its impact on administrative autonomy and the separation of state functions. The study adopts the deductive method, with a dogmatic approach, supported by a bibliographic review that articulates classical and contemporary authors in Administrative Law, Constitutional Law, and Legal Theory. The weighting of principles, as a technique of legal interpretation and application, is fundamental for assessing the legality of administrative acts, especially within the scope of discretion. The research examines the redefinition of administrative discretion under the evaluative lens of neoconstitutionalism and constitutional principles, distancing it from the idea of freedom tied to private autonomy and associating it with a legal duty of rational weighting and justification based on the established Brazilian legal order. The results indicate that neoconstitutional administrative discretion reflects political pluralism and the complexity of public administration in the Constitutional and Democratic State of Law. The research proposes that discretion cannot be understood as synonymous with freedom but rather as a normative space authorized by law and bounded by constitutional principles, good governance, and legal rationality. Judicial control, while essential, must respect the limits of administrative discretion, avoiding undue substitutions of administrative decisions. It concludes that both administrative discretion and its judicial oversight, when exercised within the normative and evaluative parameters of the legal system, promote efficient and legitimate public decisions, contributing to the consolidation of the Constitutional and Democratic State of Law and the implementation of the constitutional program